Improving Indoor Thermal Comfort on a Slant-Roofed Building with Layered Materials - Fikriarini Muchlis, Aulia; Fadhillah, Khairina; Rajib A.M., Wan; Ruby K., Mukharram (International Journal of Engineering and Technology, 2026)
Indonesia is geographically located along the equator with climatic characteristics of rainfall, relatively high humidity and sunlight inten-sity. Under these climatic conditions, we should consider to design suitable building with optimized thermal comfort. The room tempera-ture—as the main variable for such comfort—is mainly caused by the heat from sunlight retained by the roof that in turn warm up the air underneath. The hot air must be removed to achieve comfortable room temperature. Using building mockups, this experiment researchs the effect of rooftop-covering materials layered as a good insulator against heat. The method used is to compare between the sloping roof building models using clay tile rooftop as reference models and building models using a slanted roof and a combination of layered alu-minum foil and coir fiber rooftop. The application of layered roofing materials (aluminum foil and coir fiber) proved to be more effective in improving indoor comfort compared with a tile roof material commonly used in buildings in Indonesia..
Keywords: indoor thermal comfort; slant-roofed; layered material; coir fiber; bioarchitecture